A 28-Year-Old Male Patient With Right Heart Failure Due To Pulmonary Hypertension - Yuri Savitri; Wina Yunida M Siregar; Viola Septina; M Fathul Arif; Arini Nashirah; Narisha Amelia Putri (Faculty of Medicine, Universitas Diponegoro, Semarang, Indonesia, 2022)
Abstract Right Heart Failure (RHF) as a rapidly progressive syndrome with systemic congestion in the setting of impaired RV filling and/or decreased RV outflow output. A 28-year-old male patient, a photographer, lived in North Aceh was admitted to the ED of Cut Meutia Hospital. He was admitted with worsening dyspnea since 2 days before, initiated after a periode of fever. He also complained of fatigue, palpitations in ordinary activities and chest pain occasionally. He had history of presyncope and syncope. He denied any history of hypertension, type 2 diabetes, allergies, and active smoking. He had no congenital or family history of heart disease. Physical examination revealed full of conciousness with slightly abnormal vital sign. He had malar rash, dilated jugular vein. The apex of the heart shifts to the axilla anterior line, S1>S2 with systolic murmur (+). ECG showed complete RBBB with RAD and chest x-ray showed cardiomegaly. The transthoracic echocardiogram revealed severe TR (Tricuspid Regurgitation), dilatation of RARV (Right Atrium Right Ventricle), with severe PH (Pulmonary Hypertension). The patient was diagnosed with RHF (Right Heart Failure) caused by primary PH. The patient was placed on intravenous furosemide, spironolacton, digoxin, and sildenafil. Treatment and lifestyle modification were expected to improve the quality of life.